Growing tropical forage legumes in full sun and silvopastoral systems - Saulo Alberto do Carmo Araújo; Tatiana Oliveira da Silva; Norberto Silva Rocha; Marluci Olício Ortêncio (Acta Scientiarum. Animal Sciences, 2017)
Growth was evaluated three tropical forage legumes in two cropping systems: silvopastoral system (SSP) and full sun. A completely randomized design was adopted in factorial three legumes (estilosanthes cv. Campo Grande (Stylozanthes macrocephala x Stylozanthes capitata), tropical kudzu (Pueraria phaseoloides (Roxb.) Benth) and macrotiloma (Macrotyloma axillare cv. Java)) x two farming systems, with 4 repetitions. A eucalyptus SSP already deployed, with spatial arrangement of 12 x 2 m between trees was used. Legumes were planted in January 2014 a uniform cut being made in May 2014. The court assessment was carried out 125 days after the uniformity cut. There was difference for mass production of dry legumes (PMMSL) between cultivation systems, evidencing increased productivity in the farming full sun. The macrotiloma showed higher PMSL (5.29 kg DM ha-1 cut-1), while the kudzu obtained the lowest yield (3.42 kg DM ha-1 cut-1) in the sun growing full. The cultivation of legumes in SSP increased the levels of mineral matter, crude protein and neutral detergent fiber. The shade provided by the SSP caused a reduction in the mass of dry matter production, but also altered the chemical composition of the studied legumes.